Spanwise Cylinder Wake Hydrodynamics and Fish Behavior. Issue 11 (6th November 2019) - Muhawenimana, V.; Wilson, C. A. M. E.; Ouro, P.; Cable, J.
Abstract: Flows generated near hydro‐engineering structures are characterized by energetic three‐dimensional flow structures that are markedly different from naturally occurring fish habitats. The current study evaluated the interaction of Nile tilapia ( Oreochromis niloticus ) with spanwise rollers in the turbulent wake of a cylinder in both the wake bubble and the vortex shedding further downstream. The flow field hydrodynamics were measured using an acoustic Doppler velocimeter for Reynolds number ( Re D ) regimes ranging from 3, 730 to 33, 590, over a streamwise length of six diameters downstream of the cylinder, and revealed a pair of alternating vortices rotating about a spanwise axis, which were rendered asymmetric by the bed boundary proximity. Fish avoided areas where vorticity, turbulence intensity, turbulent kinetic energy, eddy size, and Reynolds shear stress were highest. Events of stability loss, referred to as spills, were significantly correlated to the turbulence integral length scale relative to fish standard length, with the peak number of spills occurring when the eddy length approached 45% to 50% of the fish length. Spill events significantly depended on Re D, Reynolds stress, and vorticity and varied according to fish length and weight. Among zones of similar Reynolds stress and vorticity magnitude, spills were most frequent when Reynolds shear stress was positive, downward acting and eddies rotated clockwise, which highlights the importance of direction and orientation of flow structures in determining the hydrodynamic forces that affect fish swimming stability. Recommendations are made for the inclusion of these metrics in the design and refinement of hydro‐engineering schemes. Key Points: The interaction of fish with spanwise vortices was examined by considering habitat use and swimming stability Fish avoided areas of highest turbulent heterogeneity, while loss of stability peaked when turbulence length scale was 45–50% of fish length Highest magnitudes of downward‐acting Reynolds stresses and negative vorticity corresponded to the highest rate of spill occurrence